Analisis Pengaruh Dividen dan Debt-to-Equity Ratio Terhadap Nilai Perusahaan dengan Ukuran Perusahaan sebagai Moderasi - Nelly Ervina; Riny; Muhammad Affar; Abdul Rosid; Adindah Novihartina Jafar (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This research aims to find empirical evidence of the influence of dividends, debt to equity ratio on company value with company size as a moderating variable. The population of this research is primary consumer goods sector companies listed on the Indonesia Stock Exchange (BEI) during the 2019-2023 pandemic. Sample selection used a purposive sampling method and obtained 150 observation data from 70 manufacturing companies listed on the Indonesia Stock Exchange (BEI). The results of this research show that dividends and debt to equity to ratio have an influence on company value. Company size is able to moderate the relationship between dividends and debt to equity ratios on company value.